2012
DOI: 10.1590/s2176-94512012000600016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of treatment with and without extractions on the growth pattern of dolichofacial patients

Abstract: Objective: The objective of this retrospective study was to compare, by means of lateral cephalograms, the facial growth pattern changes due to the treatment with and without extractions of four first premolars in dolichofacial individuals. Methods: Groups 1 and 2 were constituted of 23 dolichofacial patients each, with Class II malocclusion, division 1 and initial age average of 12.36 and 12.29 years, respectively. Patients from Group 1 were treated without extractions and Group 2 was treated with extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[24] and Katsaros [25] found no statistically signi cant difference in the skeleton values in the vertical direction between the groups that were photographed and those that were not. Although no statistically signi cant difference was found in the FMA angle between the four premolar extraction groups and the nonextraction-treated group, Porto et al [27] reported a 1.70 decrease in the SN/GoGn angle, which was statistically signi cant. In our current study, we investigated potential alterations that the chosen anchorage method, which is supposed to hypothetically have a "wedge effect," may have on a patient's vertical values following orthodontic tooth extraction.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…[24] and Katsaros [25] found no statistically signi cant difference in the skeleton values in the vertical direction between the groups that were photographed and those that were not. Although no statistically signi cant difference was found in the FMA angle between the four premolar extraction groups and the nonextraction-treated group, Porto et al [27] reported a 1.70 decrease in the SN/GoGn angle, which was statistically signi cant. In our current study, we investigated potential alterations that the chosen anchorage method, which is supposed to hypothetically have a "wedge effect," may have on a patient's vertical values following orthodontic tooth extraction.…”
Section: Resultsmentioning
confidence: 84%
“…Six studies have addressed vertical alterations in hyperdivergent people who received orthodontic tooth extraction [15,[23][24][25][26][27]. Four of these investigations involved teams of hyperdivergent people with class II skeletal abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of the present study, it seems that the effect of four premolar extraction therapy on the vertical skeletal dimension is not apparent in preadolescent and adolescent children with skeletal hyperdivergence. On the contrary, in a similar hyperdivergent class II sample, Porto et al [18] reported a statistically significant decrease in the SN-GoGn angle and facial axis (SN-Gn angle) of less than 1°in the extraction group compared with an increase of less than 1.5°in the non-extraction group. A similar beneficial effect on the anterior facial height was also noted for the extraction group compared to the non-extraction group in both class I and II patients [5].…”
Section: Discussionmentioning
confidence: 86%
“…On the contrary, in a similar hyperdivergent class II sample, Porto et al. [ 18 ] reported a statistically significant decrease in the SN-GoGn angle and facial axis (SN-Gn angle) of less than 1° in the extraction group compared with an increase of less than 1.5° in the non-extraction group. A similar beneficial effect on the anterior facial height was also noted for the extraction group compared to the non-extraction group in both class I and II patients [ 5 ].…”
Section: Discussionmentioning
confidence: 94%